2018
DOI: 10.1039/c8dt00611c
|View full text |Cite
|
Sign up to set email alerts
|

A hexa-quinoline basedC3-symmetric chemosensor for dual sensing of zinc(ii) and PPi in an aqueous mediumviachelation induced “OFF–ON–OFF” emission

Abstract: A quinoline-based C3-symmetric fluorescent probe (1), N,N',N''-((2,4,6-trimethylbenzene-1,3,5-triyl)tris(methylene))tris(1-(quinolin-2-yl)-N-(quinolin-2-ylmethyl)methanamine), has been developed which can selectively detect Zn2+ without the interference of Cd2+via significant enhancement in emission intensity (fluorescence "turn-ON") associated with distinct fluorescence colour changes and very low detection limits (35.60 × 10-9 M in acetonitrile and 29.45 × 10-8 M in 50% aqueous buffer (10 mM HEPES, pH = 7.4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…Chemosensors L1 and L2 were selective for Cu 2+ and Zn 2+ ions, respectively, most probably due to the difference in conjugation imparted by the methylene spacer. In case of L2 , rigidity of the resultant zinc complex was greatly enhanced which is the primary reason for the emission enhancement [40,43] . In contrast, when a Cu 2+ ion binds with L1 , emission quenching takes place due to its paramagnetic nature [35] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chemosensors L1 and L2 were selective for Cu 2+ and Zn 2+ ions, respectively, most probably due to the difference in conjugation imparted by the methylene spacer. In case of L2 , rigidity of the resultant zinc complex was greatly enhanced which is the primary reason for the emission enhancement [40,43] . In contrast, when a Cu 2+ ion binds with L1 , emission quenching takes place due to its paramagnetic nature [35] …”
Section: Resultsmentioning
confidence: 99%
“…In case of L2, rigidity of the resultant zinc complex was greatly enhanced which is the primary reason for the emission enhancement. [40,43] In contrast, when a Cu 2 + ion binds with L1, emission quenching takes place due to its paramagnetic nature. [35]…”
Section: Chemistryselectmentioning
confidence: 99%
See 2 more Smart Citations
“…Bhalla et al 38 have reported a hexaphenylbenzene derivative to recognise Zn 2+ in aqueous media. Out of several notable efforts at Zn 2+ sensing, 39,40 however, few are based on the ESIPT approach. 41,42 Herein, an imine (L1) and three azine (L2, L3 and L4) derivatives have been synthesised and structurally characterised by single crystal X-ray diffraction analysis.…”
Section: Introductionmentioning
confidence: 99%